Protective effect of red orange extract supplementation against UV-induced skin damages: photoaging and solar lentigines - Puglia, Carmelo; Offerta, Alessia; Saija, Antonella; Trombetta, Domenico; Venera, Cardile (Journal of cosmetic dermatology, 2014)
Summary Background Exposure of the skin to solar ultraviolet (UV) radiations causes important oxidative damages that result in clinical and hystopathological changes, contributing to premature skin aging. Hyperpigmented lesions, also known as age spots, are one of the most visible alterations in skin photoaging. Skin is naturally equipped with antioxidant systems against UV‐induced ROS generation; however, these antioxidant defenses are not completely efficient during exposure to sunlight. Oral antioxidants are able to counteract the harmful effects of UV radiation and to strengthen the physiological skin antioxidant defenses. Aims The present study was performed to evaluate the in vivo skin photo‐protecting and anti‐aging effects of a red orange (Citrus sinensis varieties Moro, Tarocco and Sanguinello) extract supplementation. Previous studies showed that red orange extracts possess strong in vitro free radical scavenging/antioxidant activity and photo‐protective effects on human skin. Materials/Methods The photo‐protective effects of red orange extract intake against UV‐induced skin erythema and melanin production in solar lentigo was evaluated on healthy volunteers by an objective instrumental method (reflectance spectrophotometry). Results Data obtained from in vivo studies showed that supplementation of red orange extract (100 mg/daily) for 15 days brought a significant reduction in the UV‐induced skin erythema degree. Moreover, skin age spots pigmentation (melanin content) decreased from 27% to 7% when subjects were exposed to solar lamp during red orange extract supplementation. Conclusions Red orange extract intake can strengthen physiological antioxidant skin defenses, protecting skin from the damaging processes involved in photo‐aging and leading to an improvement in skin appearance and pigmentation.